(untitled) (Herald of Journalism, 2023)
This article delves into the significance of artificial intelligence within the realms of film and media. Its primary objective is to unveil the diverse roles played by artificial intelligence in today’s media and film sectors while also spotlighting its unique characteristics. Consequently, contemporary society’s focus is gravitating toward the exploration of computer science as a field capable of rivaling creative professions. The study’s goal is to scrutinize the pace and potential of artificial intelligence’s evolution and to evaluate the interplay between creativity and artificial intelligence in the realm of scientific research. In this context, an analysis of the works of scientists engaged in artificial intelligence within the domain of film and media has been undertaken. At present, the matter of artificial intelligence piques the interest not only of computer science experts but also of individuals in the realms of art, literature, journalism, culture, and the humanities. This is because artificial intelligence, surpassing humans in certain technical aspects, has the potential to bestow substantial benefits upon society. However, there is apprehension that, in the future, artificial intelligence might jeopardize employment in the television and film industries. The core premise of this study involves conducting a thorough examination of the subject of artificial intelligence, pinpointing its merits and demerits, and elucidating its correlations with other domains. This elucidation will facilitate an understanding of how artificial intelligence contributes to the advancement and promotion of creative works in television and film. The analysis ultimately underscores the possibility of certain roles, such as those of journalists, directors, and actors, being supplanted by technological solutions in the foreseeable future. Artificial intelligence is dynamically evolving across diverse fields, carving out its unique identity and impact on the world. This transformation is a response to the demands of the contemporary era, and it is progressively solidifying its influence on society, thereby contributing to the advancement of information technology and the film industry.